The Case for and Against Business Assumption of Social Responsibilities. - Davis, K. (Academy of Management Journal, 1973)
There are many sound reasons both for and against business’s assumption of social responsibilities. Because of the increasing amount of rhetoric which exists on this subject, it is appropriate to e...